Genetic Analysis of Cachavirus-Related Parvoviruses Detected in Pet Cats: The First Report From China - Ji, Jun; Hu, Wen; Liu, Qiang; Zuo, Kejing; Zhi, Guanglin; Xu, Xin; Kan, Yunchao; Yao, Lunguang; Xie, Qingmei (Frontiers in Veterinary Science, 2020)
In this study, members of the Carnivore chaphamaparvovirus species 1, closely related to a virus previously reported in dog feces named cachavirus was identified for the first time in feces of Chinese cats. Screening tests using rectal swabs from 171 diarrheic and 378 healthy cats collected from Henan, Anhui, and Zhejiang provinces in China revealed two samples from diarrheic cats that were positive for cachavirus, but statistical analysis indicated no association between the presence of the virus and clinical signs (p > 0.05). Subsequently, two partial genome sequences [from nucleotides 479–4123, according to the strains from dogs (cachavirus)] of the two strains from cats (cachavirus-cat1 and –cat2) were amplified. The NS1 and VP1 sites of cachavirus-cat1 and –cat2 shared a high identity of 91.9% and 97.0% with reported cachaviruses, respectively, but lower identity of 74.8% and 73.2% with another carnivore chaphamaparvovirus named fechaviruses detected in cats, respectively, indicated the two strains might origin from dogs. These findings improve our understanding of the diversity and tropism of viruses in Carnivore chaphamaparvovirus species 1 which now include both dogs and now cats viruses.